KONSEP BAPTISAN DALAM KISAH PARA RASUL DAN EVALUASINYA TERHADAP PEMBAPTISAN VIRTUAL - Hasibuan, Serepina Yoshika; Walean, Rudy Roberto; Larosa, Setiaman (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2022)
One form of church service activity during social restrictions during the COVID-19 pandemic is online or virtual baptism. This virtual baptism has received criticism because it does not follow the Bible's teaching about baptism, especially the Acts concept. This study intends to reveal the Acts concept of baptism and then use it to evaluate the practice of virtual baptism. The research method used is a hermeneutic analysis using research results or studies from other researchers. The object of study is the narrative of the baptism of Peter, Philip, Ananias, and Paul. The results showed that: 1) firstly, baptism is a passive act, so it cannot be done only by the baptismal candidate; 2) baptism is carried out directly involving two parties, both the baptist and the person being baptized; 3) baptism must fulfill the koinonia in the worship of the people. Therefore, virtual baptism is irrelevant even in pandemic conditions.